The role of intravascular physiological assessment of the significance of coronary involvement in patients with severe aortic stenosis - K. V. Petrosyan; A. V. Abrosimov; E. S. Goncharova; M. A. Chobanyan (Российский кардиологический журнал, 2024)
As technology improves, the number of transcatheter aortic valve implantation (TAVI) procedures performed is steadily increasing. Due to the comparable outcomes with surgical treatment of aortic stenosis, TAVI is increasingly being performed in a group of younger patients. In this connection, there is an increasing need for a reasonable approach to assessing the severity of concomitant coronary lesions. Non-invasive studies in this group of patients have low sensitivity and specificity in identifying significant coronary narrowing. In addition, the use of stress testing is limited by the risks of potential complications due to the severity of patients with critical aortic stenosis. The assessment of fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR), which has become widespread in isolated coronary heart disease (CAD), in the case of a combination of CAD with aortic stenosis, requires careful study and analysis. The literature review shows that today there are the first results of using the assessment of coronary physiology to determine indications for myocardial revascularization in patients with aortic stenosis. New threshold values of FFR and iFR applicable for patients in this group are considered. The results of literature data indicate the need for large randomized studies to better understand the method capabilities and develop the most optimal approach to the treatment of TAVI candidates with concomitant CAD.